Comparative Analysis of Financial Practices Between Nepali Non-Profits and Established U.S. Non-Profits: A Study of Governance and Transparency - Siwakoti, Bhola Nath (Digital Repository of Theses - SSBM Geneva, 2025)
This research compares the financial management methods of Nepali NPOs to those of US non-profits. Non-profits provide social services, education, and community development worldwide; however, governance structures and financial transparency significantly impact their practical sustainability. Many issues hinder Nepali NPOs in the diaspora. These include cultural norms, fiscal limits, volunteerism, and US legal complexities. This research will analyse the accountability, transparency, and sustainability challenges faced by Nepali charitable groups, identify financial governance and reporting difficulties, and provide recommendations for addressing these issues. The author has 25 years of experience in charity leadership and employs a current mixed-methods approach. Organisational financial records like income statements, balance sheets, and tax filings provide quantitative data. We interviewed Nepal’s non-profit leaders, including board members, donors, and heads, to gather qualitative data. The research addresses four main questions: How do US-based Nepali charity organisations handle finances? How do these difficulties compare to those faced by US charitable groups? Why do Nepali NPOs often fail to maximise their limited financial resources? What financial and governance initiatives might boost organisational performance? The research indicates that Nepali charitable organisations typically lack financial expertise and effective governance. Limited budgeting, financial recordkeeping, and conformity with US non-profit regulations are difficulties. Cultural traditions can impact leadership and financial reporting, potentially hindering accountability and transparency. In contrast, US nonprofits are known for their strict governance and financial transparency, as required by the IRS Form 990. This research invests in capacity-building initiatives, standardises governance frameworks, and improves financial literacy among NPO CEOs in Nepal. Budgeting, compliance, donor reporting, and financial management software training are proposed. The research emphasises the necessity for culturally responsive government policies that respect Nepali customs and US law. Comparative analysis promotes non-profit financial management. This helps immigrant-led groups analyse and improve their methods, a major contribution. This information is also useful for companies, financiers, and legislators who benefit non-profits. This research aims to align Nepali NPOs’ goals with their activities, thereby enhancing their financial stability and reputation in the US. The research surveyed 15 prominent US nonprofits and 20 Nepali non-profits, and the findings revealed significant disparities in compliance, budgeting accuracy, and financial management. U.S. organizations consistently demonstrated greater donor reporting and regulatory conformity, but Nepali NPOs faced institutional and cultural obstacles to transparency. Future research should focus on culturally relevant financial training programs that include both U.S. compliance rules and the beliefs of the Nepali community. Comparative longitudinal studies might track improvements in governance and transparency over time. To identify broader patterns in diaspora financial management, the sample could be expanded to include other immigrant-led nonprofits. Finally, integrating digital financial tools into experimental pilots might assess their impact on regulatory compliance, donor confidence, and budgeting accuracy in resource-constrained contexts. These initiatives would provide practical strategies to enhance the profitability and legitimacy of charitable organizations managed by diaspora members, while also advancing academic understanding of cross-cultural non-profit governance.